The Utilization of Home Yard Medicinal Plants by Traditional Healers (Battra) in Pentek Village, Sadaniang District of Mempawah Regency - Irwan Pirmansyah; Fathul Yusro; Yeni Mariani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Currently, people still choose traditional medicine as one of the options to maintain their health. This conventional medicine uses ingredients from wild plants taken from the forest or plants grown in the home yard. Although the forest provides various medicinal plants, many are currently cultivated in the yard for easy access when needed. This study aims to analyze medicinal plants in the home yard used by Battra in Pentek Village, Sadaniang District, Mempawah Regency. This study used a survey method by conducting interviews with all Battra in Pentek Village. We then analyzed plant species, habitus and parts of plants used, processing methods, usage methods, and state of concoction. The results showed that Battra in Pentek Village used 37 medicinal plants in their home yards, with the most widely used plant family being Zingiberaceae (5 species). The most frequently used plant habitus was herb (56.76%), and the most commonly used plant part was leaves (28.81%). The processing method used was boiling (37.14%), and the usage method was drinking (39%)—the form of concoction used as a mixture (70.27%).